Function and Regulation of Human Terminal Uridylyltransferases - Yashiro, Yuka; Tomita, Kozo (Frontiers in Genetics, 2018)
RNA uridylylation plays a pivotal role in the biogenesis and metabolism of functional RNAs, and regulates cellular gene expression. RNA uridylylation is catalyzed by a subset of proteins from the non-canonical terminal nucleotidyltransferase family. In human, three proteins (TUT1, TUT4, and TUT7) have been shown to exhibit template-independent uridylylation activity at 3′-end of specific RNAs. TUT1 catalyzes oligo-uridylylation of U6 small nuclear (sn) RNA, which catalyzes mRNA splicing. Oligo-uridylylation of U6 snRNA is required for U6 snRNA maturation, U4/U6-di-snRNP formation, and U6 snRNA recycling during mRNA splicing. TUT4 and TUT7 catalyze mono- or oligo-uridylylation of precursor let-7 (pre–let-7). Let-7 RNA is broadly expressed in somatic cells and regulates cellular proliferation and differentiation. Mono-uridylylation of pre–let-7 by TUT4/7 promotes subsequent Dicer processing to up-regulate let-7 biogenesis. Oligo-uridylylation of pre–let-7 by TUT4/7 is dependent on an RNA-binding protein, Lin28. Oligo-uridylylated pre–let-7 is less responsive to processing by Dicer and degraded by an exonuclease DIS3L2. As a result, let-7 expression is repressed. Uridylylation of pre–let-7 depends on the context of the 3′-region of pre–let-7 and cell type. In this review, we focus on the 3′ uridylylation of U6 snRNA and pre-let-7, and describe the current understanding of mechanism of activity and regulation of human TUT1 and TUT4/7, based on their crystal structures that have been recently solved.